Geological-geotechnical investigations of the historical Diriyah urban zone in Riyadh, Saudi Arabia: an integrated approach - Abdelrahman, Kamal; Hazaea, Saddam Ali; Almadani, Sattam A. (Frontiers in Earth Science, 2023)
One hundred seventy geotechnical boreholes, two geoseismic profiles of multichannel analyses of surface waves (MASW), and two geoelectrical cross-sections of electrical resistivity tomography (ERT) were carried out in the historical Diriyah urban zone. The borehole samples were analyzed for the geotechnical parameters of the standard penetration test (SPT N-value), the rock quality designation (RQD), and compressive strength (CS). Moreover, P- and S-wave velocities have been calculated. The measured SPT N-value has been corrected to amend the N60 parameter. According to the corrected N60, type, lithological, and soil profiles were divided into five distinct subsurface layers. It is indicated, for all recorded depths, these sediments become denser with depth where the values of N60 increase from 5 to 88 downward. According to grain size distribution, the major part of soil sites is composed of sand and varies from low to medium compressibility. The estimated RQD values range from 5 to 100 indicating rocks with significant variations in their geotechnical and physio-chemical characteristics. Furthermore, the compressive strength varies widely between 152.3 and 1104.2 kg/cm2, which represents diverse geodynamic behavior under civil engineering constructions. Besides, the range of soil stiffness is indicated by the Shear-wave velocity (Vs) for soil layers, which varies from 171.3 to 456.2 m/sec. According to the findings of the MASW profiles, the shear wave velocity is shown to be decreasing in MASW profile 1 between depths of 8 and 14 meters, where the values range from 1000 to 1500 m/s, indicating a weak zone filled with secondary materials. But line 2 shows how the shear wave velocity decreased from depths of 5 m to 11 m, where values ranged from 1000 to 1500 m/s, thus indicating a weak zone. The low resistivity zones in ERT cross-sections, which are found at the same depths in MASW profiles, are well associated with these findings. It can be concluded that there are a number of weak zones with varying depths, shapes, and dimensions found in the historical Diriyah urban zone's near-surface deposits that civil engineers, urban planners, and urban developers should consider before undertaking any construction or developmental work involving civil engineering.